Does Good Design Matter in the Seedstock Advertising Business? Effects of Graphic Design in Beef Seedstock Ads on Cattle Producers’ Trust and Credibility - Morgan L Marley; Katie M Abrams; Daniela Castillo (Journal of Applied Communications, 2019)
Designers are trained professionals who understand how to effectively visually communicate based on executing principles of design and an understanding of their audience. Within the beef seedstock industry, ad design varies widely in terms of technical effectiveness, but how do those differences affect potential customers? This study tested the effects of seedstock ad’s graphic design on the viewer’s trust and credibility among 561 Angus cattle producers. Our results show the graphic design of a beef seedstock ranch ad promoting an upcoming bull sale did not influence producers’ perceptions of trust and credibility. However, results did reveal better designed ads are positively related to producers’ trust of that brand. We suggest the study results were influenced by a first impression established through the brand description presented to all treatment groups, which illustrates beef seedstock buyers may be more reliant on other informational cues than design to inform their purchasing decisions. Future research is needed to parcel out effects of the brand information relative to the design aspects of the ad.
Keywords: Graphic design; design principles; design effects; visual communication